S. Kahn. Kant and the trolley / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The article explores the applicability of Kant’s ethics, which prohibited the use people as mere means, in solutions to various Trolley problem scenarios. Based on the distinction between notions ‘using as mere means’ and ‘treating as mere means’, the precise requirements of Kant’s prohibition are reconstructed.